The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.2147/dmso.s368867
|View full text |Cite
|
Sign up to set email alerts
|

Yishen Capsule Alleviated Symptoms of Diabetic Nephropathy via NOD-like Receptor Signaling Pathway

Abstract: To explore the mechanism of Yishen capsule against diabetic nephropathy (DN) based on the analysis of transcriptomics. Material and Methods: SD rats (Male, SPF grade) were randomly divided into four groups, the normal group, the DN group, the Yishen capsule group and the resveratrol group. Urine and renal tissue samples were collected after feeding with physiological saline and above drugs for 8 weeks. 24-hour urine microalbumin protein was detected by ELISA. HE staining and PAS staining were performed on rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Yishen capsule is a Chinese herb compound preparation that has been used for decades in the First Affiliated Hospital of Shanxi Medical University (137,138). In previous studies, it has been found that Yishen capsule restored podocyte foot process effacement (137) and alleviated renal inflammation by regulating NOD-like receptor signaling pathway in DKD mice (139). A recent study has found that, Yishen capsule improved renal injury by promoting podocyte autophagy via the SIRT1/NF-kB pathway in STZ-induced DKD rats (18).…”
Section: Chinese Herb Compound Preparations In Regulating Autophagy O...mentioning
confidence: 99%
“…Yishen capsule is a Chinese herb compound preparation that has been used for decades in the First Affiliated Hospital of Shanxi Medical University (137,138). In previous studies, it has been found that Yishen capsule restored podocyte foot process effacement (137) and alleviated renal inflammation by regulating NOD-like receptor signaling pathway in DKD mice (139). A recent study has found that, Yishen capsule improved renal injury by promoting podocyte autophagy via the SIRT1/NF-kB pathway in STZ-induced DKD rats (18).…”
Section: Chinese Herb Compound Preparations In Regulating Autophagy O...mentioning
confidence: 99%